2015
DOI: 10.1007/s11242-015-0552-3
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Pole Approximation to Interfacial Mass Transfer in Porous Media Augmented with Bulk Reactions

Abstract: We study interfacial mass transfer between two immiscible fluids in porous media augmented with bulk reactions. A closed-form analytic approximation derived through Laplace transformation is represented for Darcy-Brinkman flow in the presence of firstorder bulk reactions represented by the Damköhler number (Da). By comparing the residues of all the singularities, it is shown that the main contributor to the solution is the simple pole of the equations. We show that the solution holds for a range of Da.Pe < 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This is seen to be feasible through systematic upscaling of both experimental and computational studies from nano- to microscales. Indeed, similar to the momentum field for which the Darcy law has been amended by further terms for special cases (e.g., Darcy–Forchheimer and Darcy Brinkman for inertia and friction, respectively), it might be possible to include terms in the Darcy scale mass transport equation. Where NAPLs also coexist (including DNAPLs , ), this is particularly challenging, but such occurrences are common and warrant investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is seen to be feasible through systematic upscaling of both experimental and computational studies from nano- to microscales. Indeed, similar to the momentum field for which the Darcy law has been amended by further terms for special cases (e.g., Darcy–Forchheimer and Darcy Brinkman for inertia and friction, respectively), it might be possible to include terms in the Darcy scale mass transport equation. Where NAPLs also coexist (including DNAPLs , ), this is particularly challenging, but such occurrences are common and warrant investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Teramoto and Chang [15], Mackay et al [23], Huntley and Beckett [24], and Thornton et al [25], among others, demonstrated that the continuous loss of water-soluble compounds leads to continuous depletion of LNAPL in the source zone. Actually, there are a large number of analytical and numerical approaches, varying in scale and complexity, to simulate NAPL dissolution into the aqueous phase [18,[26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most of these approaches are based on empirical Sherwood-Gilland models that do not consider explicitly the NAPL/water interface area and were exclusively validated by lab-scale experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Such spectrum is very broad ranging from the revelation of homotopy analysis (Liao, 1992;Liao, 1999;Bég et al, 2012;Malvandi et al, 2014;Hassan andRashidi, 2014 andMakukula andMotsa, 2014), differential transforms (Rashidi et al, 2013 andGanji et al, 2016) and Adomian decompositions (Adomian, 1994;Wang, 2004;Aski et al, 2014 andAkpan, 2015) to a combination of these and analogous techniques (e.g., coupled integral transform and functional analysis (Lari and Moeini, 2015) and the joined differential transform method with the Padè approximants (Rashidi et al, 2013 andThiagarajan andSenthilkumar, 2013). An important outcome was investigation into more complex physical problems.…”
Section: Introductionmentioning
confidence: 99%